Influence of Adventure Race Disciplines on the Overall Performance during 35 to 50-km Races - Bruna Santana Silva; Claudio Alexandre Gobatto; Fúlvia de Barros Manchado-Gobatto; Larissa Mayara Pereira Sulinski; Taisa Belli (Universidade Estadual Paulista (UNESP), 2020)
Abstract Aims: This study aims to analyze the influence of adventure race disciplines on the overall performance during 35 to 50-km competitions. Methods: Twenty-four athletes from twelve teams were studied during the second (Jacarei-SP, Brazil, 44.5-km) and fourth (Passa Quatro-MG, Brazil, 37.1-km) races of the 2015 Haka Race Series, which comprised Brazilian Adventure Race Ranking. We analysed the relationship between disciplines velocities and overall race velocity of the teams during each competition. Results: We observed the race velocity of the teams during second race was significantly (P < 0.05) correlated with the first (R=0.80) and last (R=0.65) split velocities of trekking, and with the last split velocity of mountain biking (R=0.73). On the other hand, the race velocity of teams during fourth race was significantly (P < 0.05) correlated with the split velocity performed during the course of water trekking with trekking (R=0.96). Conclusion: Greater performance of the athletes in the disciplines of mountain biking, trekking and water trekking is related to their overall performance during 35-50 km ARs. In addition, the influence of adventure race disciplines is specific to the overall performance during different competitions.